A Landmark in Turbulent Times: The Meaning and Relevance of the Synod of Dordt (1618–1619) - Jong, K. W. de; Vlastuin, W. van; Selderhuis, Herman J.; Brown, Christopher B.; Frank, Günter; Mahlmann-Bauer, Barbara; Rasmussen, Tarald; Soen, Violet; Tóth, Zsombor; Wassilowsky, Günther; Westphal, Siegrid; Ryrie, Alec; et al. (Refo500 Academic Studies (R5AS), 2022)
At the Synod of Dordrecht (1618–19), the deep questions of justification and faith, election and rejection, time and eternity, grace and free will, the individual and the body of Christ, Israel and the church, the acquisition of salvation through Christ and its application by His Spirit, baptism and regeneration, and especially the precise relationship between these, were at stake. These deep questions are addressed in this study. Lines are drawn to the historical, theological and political context of the time of the synod. Patristics and the Middle Ages are not absent, nor are the metaphysical questions related to these theological issues. Also the church polity of Dordt is discussed, especially the roots, influences and structures of its church order. This volume ends with a hermeneutical reflection on the way we confess the electing God today.